ANALISIS KEAMANAN VOICE OVER INTERNET PROTOCOL (VOIP) OVER VIRTUAL PRIVATE NETWORK (VPN) - Dwi Prastantio Putra (Universitas Teknokrat Indonesia, 2021)
This research was conducted on the basis of the influence of security systems that play a role in encrypting data on VoIP communication systems, with the security technology of PPTP VPN computer networks with the system passing data in a virtual private ip or as a tunnel for secure data transmission media. The results obtained from security analysis for the implementation of security methods on PPTP VPNs, then the data to help developers in terms of building a secure VoIP communication system. Basiclly ZRTP uses the Diffie-Hellman key exchange as a key exchange of communication between clients, which is the key for communication between clients using hashes from Diffie-Hellman and is done peer-to-peer through the VOIP RTP package, while the Point-to-Point Tunneling Protocol (PPTP) is a network protocol that allows the secure transmission of data from the remote client to the server by creating a virtual private network (VPN) through a network of data. TCP/IP or UDP is dedicated to encryption and creates RTP tunnel transport on VoIP communication systems. VoIP communication system research is conducted using 2 security methods, namely VoIP VPN PPTP, VoIP ZRTP, with the aim to find out the results of VoIP communication testing using PPTP and ZRTP VPN security methods if an attack occurs during VoIP communication